Hubungan Status Gizi Ibu Saat Hamil dan Riwayat Pemberian Asi Eksklusif dengan Kejadian Stunting di Wilayah Kerja Puskesmas Wanareja 1 Kabupaten Cilacap Tahun 2023 - Yogi Andhi Lestari; Neni Fitriyana (Universitas Pahlawan Tuanku Tambusai, 2023)
The prevalence of stunting in Indonesia in 2022 was 21.6%, which still exceeds the tolerance limit set by the WHO. The high prevalence of stunting cases in Indonesia indicates that the overall health status of the Indonesian population remains low. This research used a case-control study design with a population of 99 stunted children and 99 normal children. The research instrument employed a checklist and the statistical test used was the chi-square test. The results showed that in the working area of Puskesmas Wanareja 1, approximately 37.4% of pregnant mothers experienced Chronic Energy Deficiency (CED), compared to about 6.1% in the control group. There were 52.5% of children in the case group who had never received exclusive breastfeeding, while only 33.3% in the control group faced a similar situation; 66.7% of children in the control group had received exclusive breastfeeding. The incidence of stunting in this area reached 99 individuals out of a total population of 3,675. There was a correlation between maternal nutritional status during pregnancy and stunting, as mothers with inadequate nutritional status during pregnancy had a 9.25 times greater chance of giving birth to stunted children compared to mothers with good nutritional status. There was also a relationship between the history of exclusive breastfeeding and stunting, where children who did not receive exclusive breastfeeding had a 2.213 times higher chance of experiencing stunting compared to those who received exclusive breastfeeding. Keywords: CED, Stunting, Exclusive Breastfeeding